THE URGENCY OF ENACTING PERSONAL DATA PROTECTION LAW AS A PATRONAGE FROM THE DEVELOPMENT OF COMMUNICATION AND INFORMATION TECHNOLOGY IN INDONESIA - Ghansham Anand; Agus Yudha Hernoko; Antonius Gunawan Dharmadji (Perspektif, 2020)
The development of information technology might control the pattern of people’s behavior in digital era. The presence of internet as the main platform for online activities, including electronic transactions, was now increasingly attracting the interest of Indonesian people although it was vulnerable to be hacked by irresponsible parties as a cyber-attack. One cyber-attack targets individual’s personal data. This study, therefore, took some issues related to that matter. First, it discussed the regulation of personal data protection in Indonesia applied in recent days, and second, it proposed an appropriate law to regulate such issue in the future.This study was a normative research with statute and case approaches. The result showed that, first, the existing regulation for personal data protection was less effective as it was still scattered in some sectorial setting, and thus, the system of appropriate regulation under a comprehensive law was considerably important. Second, the disharmony of regulatory legislation in regulating people personal data protection needed to be solved through a specific regulation which particularly regulated on personal data protection.